Meningkatkan Resiliensi Penyakit Kronis dengan SEFT (Spiritual Emotional Freedom Technique) - Purnamayanti, Ni Kadek Diah; Winaryanta, Made Deisyana; Jansen, Madelief (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
Background: Non-communicable chronic diseases are currently a global health problem. Treatment of chronic diseases is serious because it can affect the patient's quality of life and consume quite a large amount of treatment funding. However, pharmacological treatment cannot be effective if chronic disease patients are unable to manage stress. For this reason, therapeutic modalities are needed that are able to treat patients as a whole, both bio-psycho-social and spiritual, one of which is the spiritual emotional freedom technique (SEFT). Purpose: This community service activity aims to increase the resilience of chronic disease patients through SEFT training. Method: Activities were provided for posyandu cadres in Kayuputih Village, Sukasada I Community Health Center Working Area. The training method was carried out by giving lectures, demonstrations, guided re-demonstrations, providing media, and evaluation. Results: SEFT is a non-pharmacological therapy that is acceptable to participants. SEFT can be done independently with the guidance of media leaflets and video demonstrations. SEFT is considered a unique way of praying and is modified by healing efforts by tapping specific points on the body. Conclusion: SEFT can be an alternative choice for chronic disease patients to maintain resilience in long-term self-care.